İLKOKUL YÖNETİCİLERİNİN PROGRAM LİDERLİĞİ DAVRANIŞLARINI GÖSTERME DÜZEYLERİNİN ÖĞRETMENLERİN KOLEKTİF YETERLİK ALGISINA VE ÖRGÜTSEL ÖĞRENME DÜZEYİNE ETKİSİ - YARAŞ, ZÜBEYDE (Fırat Üniveristesi, 2013)
Bu araştırmanın genel amacı; ilkokul yöneticilerinin program liderliği davranışlarını gösterme düzeylerinin kolektif yeterlik algısına ve örgütsel öğrenme düzeyine olan etkisini belirlemektir. Bu amaçla araştırmada veri toplama aracı olarak üç ölçek kullanılmıştır. Bunlar; Demiral (2009) tarafından geliştirilen ?Program Liderliği Ölçeği?, Kurt (2009) tarafından Türkçe? ye çevirisi yapılmış ?Kolektif Yeterlik Ölçeği? ve Yavaş (2012) tarafından geliştirilmiş ?Örgütsel Öğrenme Ölçeği? dir. Araştırma Batman İli merkez ilçe sınırları içinde görev yapan 510 sınıf öğretmeni üzerinde yürütülmüştür. Veriler yüzde, frekans, aritmetik ortalama, Bağımsız gruplar t- testi, Tek Yönlü Varyans Analizi (ANOVA), Korelasyon Analizi ve Çoklu Regresyon Analizi teknikleri kullanılarak çözümlenmiştir. Araştırmanın sonucunda; okul büyüklüğüne göre (öğretmen sayısı) yöneticilerinin program liderliği davranışlarını gösterme düzeylerinin, kolektif yeterlik algısının ve örgütsel öğrenme düzeyinin anlamlı düzeyde farklılaştığı belirlenmiştir. Cinsiyet değişkenine göre ise, program liderliği, kolektif yeterlik algısı ve örgütsel öğrenme düzeyine ilişkin görüşlerin anlamlı düzeyde farklılaşmadığı tespit edilmiştir. Yapılan korelasyon analizi sonuçlarına göre; ilkokul yöneticilerinin program liderliği davranışları ile öğretmenlerin kolektif yeterlik algısı ve öğretmenlerin örgütsel öğrenme düzeyi arasında istatistiki olarak anlamlı ilişki olduğu sonucuna ulaşılmıştır. Ayrıca, ilkokul yöneticilerinin program liderliği davranışlarının öğretmenlerin Kolektif yeterlik algısının ve örgütsel öğrenme düzeyinin anlamlı bir yordayıcısı olduğu yapılan çoklu regresyon analizleri sonucunda tespit edilmiştir. Bu sonuçlara göre gerek politika üretenlere, gerek uygulayıcılara ve gerekse araştırmacılara öneriler getirilmiştir. Anahtar Kelimeler: Liderlik, program liderliği, Kolektif yeterlik, örgütsel öğrenme

The overall objective of this thesis is to determine the effect of demonstration level of program leadership behaviors among elementary school administrators on perceptions of collective efficacy and organizational learning. Three instruments were used for this purpose and as a means of data collection in research. These are, respectivey, the "Program Leadership Questionnaire" developed by Demiral (2009), the "Collective Efficacy Scale" by Kurt (2009) as in its Turkish translation, the "Organizational Learning Scale" developed by Yavaş (2012). The research has been conducted among 510 classroom teachers who work within the boundaries of the central district of Batman Province. The data has been analyzed by using analysis techniques such as percentage, frequency, , arithmetic mean, independent samples t-test, One-Way Analysis of Variance (ANOVA), Correlation analysis and multiple regression Analysis. As a result of this study, it has been identified that the demonstration level of program leadership behaviors among elementary school administrators on perceptions of collective efficacy and organizational learning significantly differentiated according to the size of schools (number of teachers). Moreover, according to Gender Variable, it has been found that program leadership, perception of collective efficacy, views about the level of organizational learning have not been significantly differentiated. According to the results of the correlation analysis, it has been concluded that there is a statistical significant relationship between program leadership behaviors of elementary school administrators and teachers? perception of collective efficacy as well as the level of organizational learning for the teachers. Additionally, it has been identified that the program leadership behaviors of elementary school administrators is a significant predictor of teachers? perception of collective efficacy and the level of organizational learning for the teachers. Based on the findings of this thesis, relevant recommendations have been made for the policy makers, as well as researchers and practitioners in this field. Keywords: Leadership, Program leadership, Collective efficacy, Organizational learning
The effect of demonstration level of program leadership behaviors among elementary school administrators on collective efficacy perception and organizational learning
Keywords: Eğitim ve Öğretim